2019
DOI: 10.32718/nvlvet9407
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and epizootic roles of Golden jackal, genus Canis aureus in the Northwest of Black Sea coast

Abstract: Penetration of jackal, typical representative of Asia Minor-Balkan group, genus Canis aureus into the territory of the Northwest Black Sea coast - has become a rather unexpected phenomenon and led to environmental, zoogeographical and epizootic issues. The last one may lead to the development of potentially dangerous epizootic processes, the assessment of the threat and possible consequences require systematic researches. The purpose of this work was to study the ecological and epizootic role of Canis aureus i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The seroprevalence of antibodies against leptospiral serovars found in this study was comparable to the seroprevalence reported in golden jackals from Ukraine (100%; 9/9). Both golden jackals tested had titres against five serovars [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The seroprevalence of antibodies against leptospiral serovars found in this study was comparable to the seroprevalence reported in golden jackals from Ukraine (100%; 9/9). Both golden jackals tested had titres against five serovars [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence was slightly lower than recorded among red foxes from Croatia (57.6%) (Milas et al, 2006). In a recently conducted study on jackals, Nakonechnyi et al (2019) found positive reactions against Leptospira interrogans among all nine animals that were tested.…”
Section: Discussionmentioning
confidence: 97%
“…4). The peaks of rabies epidemic in fox populations in autumn and winter (from October to February) are driven mainly by fox ecology, with peak numbers of cases coinciding with fox resettlement due to breeding, habitat expansion and aggressive behaviour which facilitates fighting over territory (28,31). Fluctuations in fox numbers also depend on the availability of food and the number of infected individuals in the population (5).…”
Section: Fig 3 Collection Of Domestic Carnivore Samples By Oblast In 2012-2018mentioning
confidence: 99%
“…Although culling occurs throughout Ukraine, each oblast regulates the cull differently, and hence large regional variation in fox population density across Ukraine. Although veterinary and sanitary requirements aim at a fox population density of 0.5-1 head per 1000 ha at the end of culling, fox population density in most oblasts (in the western and central parts of Ukraine) exceeds that rate up to 3-3.5 head per 1000 ha (31). The culling foxes for evaluation of the effectiveness of ORV, which was conducted by hunters mainly in autumn in different numbers, also influencing the reporting efforts depending on each oblast.…”
Section: Fig 3 Collection Of Domestic Carnivore Samples By Oblast In 2012-2018mentioning
confidence: 99%
See 1 more Smart Citation